Mononuclear phagocyte system blockade using extracellular vesicles modified with CD47 on membrane surface for myocardial infarction reperfusion injury treatment. (August 2021) - Wei, Zilun; Chen, Zhaoyang; Zhao, Yongchao; Fan, Fan; Xiong, Weidong; Song, Shuai; Yin, Yong; Hu, Jingjing; Yang, Kun; Yang, Lebing; Xu, Biao; Ge, Junbo
Abstract: Mesenchymal stem cell (MSC)-derived extracellular vesicles (EVs) with anti-apoptotic and anti-inflammatory properties have been intensively studied. However, rapid clearance by the mononuclear phagocyte system remains a huge barrier for the delivery of extracellular vesicle contents into target organs and restricts its wider application, particularly in the heart. CD47 is a transmembrane protein that enables cancer cells to evade clearance by macrophages through CD47 − signal regulatory proteinα binding, which initiates a "don't eat me" signal. This study aimed to explore the biodistribution and delivery efficiency of EVs carrying the membrane protein CD47 and specific anti-apoptotic miRNAs. EVs were isolated from MSCs overexpressing CD47 (CD47-EVs) and identified. Fluorescence-labeled EVs were injected through the tail vein and tracked using fluorescence imaging. In silico analysis was performed to determine miRNA profiles in MSCs and in a heart-derived H9c2 cardiomyoblast cell line under hypoxia vs. normoxia conditions. Electro CD47-EV was constructed by encapsulating purified CD47-EV with miR-21a via electroporation. The effect of miR21-EVs on the pro-apoptotic gene encoding phosphatase and tensin homolog (PTEN) was evaluated by dual-luciferase assay, qPCR, and western blotting. Exogenous miR21 distribution, PTEN protein level, blood vessel density, anti-apoptotic effect by TdT-mediated dUTP nick-end labeling staining, and macrophage and leukocyte infiltration in the myocardium were assessed by immunofluorescence staining. Cardiac functional recovery during the early stage and recovery period was evaluated using echocardiography. The results showed that CD47-EVs were still detectable in the plasma 120 min after the tail vein injection, compared to the detection time of less than 30 min observed with the unmodified EVs. More strikingly, CD47-EVs preferentially accumulated in the heart in the ischemia-reperfusion (I/R) + CD47-EV group [heart total fluorescence radiance ( × 10 5 Photons/sec/cm 2 /sr) 51.62 ± 11.30 v.s. 10.08 ± 3.15 in the I/R + unmodified EVs group] 8 h post-injection. Exogenous miR-21 is efficiently internalized into cardiomyocytes, inhibits apoptosis, alleviates inflammation, and improves cardiac function. In conclusion, electro CD47-EVs efficiently improve biodistribution in the heart, shedding new light on the application of a two-step EV delivery method (CD47 genetic modification followed by therapeutic content electrotransfection) as a potential therapeutic tool for myocardial I/R injury that may benefit patients in the future.